Signs of ‘New Sincerity’ Literature in Vanessa Dieffenbach’s Novel “The Language of Flowers” - S. G. Gorbovskaya (Научный диалог, 2023)
The theme of ‘new sincerity’ in literature is considered on the material of the novel “The Language of Flowers” by the American writer Vanessa Dieffenbach, published in 2011. The relevance of the study lies in the keen interest of literary scholars in the 21st century to the issues of ‘new sincerity’ and florpoetics. It is shown that in Dieffenbach modern novel, these themes are revealed through the reconstruction of the ancient secular tradition and the literary genre “language of flowers”. The author of the article traces the history of the formation of ‘new sincerity’ literature at the end of the XX — early XXI centuries. On the example of V. Dieffenbach’s novel, signs of ‘new sincerity’ literature are revealed in fragments of the novel related to the “language of flowers” (as floral communication between heroes), the botanical theme and the recreation of the novel heroines of the forgotten literary genre history of the 19th century with the corresponding name. It has been established that in the past the “language of flowers” was necessary to veil one’s feelings, and in the present, when people lack live communication, it helps to open up. In the conclusion, the author of the article points out the features that characterize V. Dieffenbach’s novel as the literature of ‘new sincerity’. Among them are the emotionality of the text, the search for new means of communication between people, the appeal to Christian values and the tradition of the “language of flowers”, which helps people communicate with each other.